The obstacles hierarchy of school disaster preparedness implementation in Mount Sinabung area, Indonesia - Muzani, Muzani; Fatimah, Anggun Nadia; Imsa, Mentari Anugrah; Casmana, Asep Rudi (Frontiers in Education, 2022)
The incidence of natural disasters has an impact on various sectors of life, including the education sector. Schools as educational facilities are considered vulnerable areas that need handling steps to reduce disaster risk. As one of the most vulnerable countries to natural disasters, Indonesia already has several policies and programs from the government to address these problems. However, several studies have shown that the implementation did not go according to plan. These studies also reveal that this implementation lies in the local context in which the program or policy is implemented. That is why the study aims to examine the school disaster preparedness implementation in the Mount Sinabung area as one of the disaster-prone areas in Indonesia. This research utilizes the Interpretative Structural Modelling approach to build a hierarchy and classification of obstacles in implementing school disaster preparedness around that area. Data are collected through a combination of observation, interview, and survey techniques in 2017 and 2018 that involved a total of 35 participants. The result showed fourteen sub-elements identified as limiting factors of school preparedness implementation in the Mount Sinabung area. Three elements serve as the first level (or the basis/key element) of the obstacles hierarchy: integration of subject, school policy, and school curriculum. Intervention at the base level will trigger changes and give impact the other upper-four levels of elements. This hierarchy and classification are relevant to the context of the Mount Sinabung eruption and cannot be applied in other areas. This research did not measure the numeric data per sub-element in disaster preparedness. Therefore, the limitations of this study can be directions for future research to examine the implementation in another area by using numeric data. The results of this study also provide major recommendations to several stakeholders. The existing policies regarding school disaster preparedness and their implementation need to be reviewed to improve the result.